Development of Sharia-Based Ecotourism in Pagar Alam City (Potential and Strategy in Utilizing Natural Resources Sustainably) - Alamsyah, Syahril Ramadhon (Civiliza Publishing, 2024)
Sharia integration in ecotourism means combining the basic principles of ecotourism such as nature conservation and local community empowerment with sharia rules. The development of ecotourism in Pagar Alam is a strategic opportunity, not only to increase the income of local communities, but also to support environmental conservation efforts and cultural heritage. In addition, with the increasing interest in sharia-based tourism, Pagar Alam has a great opportunity to attract Muslim tourists through the development of ecotourism destinations that are in accordance with Islamic principles.